2003
DOI: 10.1084/jem.20022041
|View full text |Cite
|
Sign up to set email alerts
|

By Altering Ocular Immune Privilege, Bone Marrow–derived Cells Pathogenically Contribute to DBA/2J Pigmentary Glaucoma

Abstract: Pigment dispersion syndrome causes iris pigment release and often progresses to elevated intraocular pressure and pigmentary glaucoma (PG). Because melanin pigment can have adjuvant like properties and because the Gpnmb gene, which contributes to pigment dispersion in DBA/2J (D2) mice, is expressed in dendritic cells, we tested the hypothesis that ocular immune abnormalities participate in PG phenotypes. Strikingly, we show that D2 eyes exhibit defects of the normally immunosuppressive ocular microenvironment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 28 publications
1
110
0
Order By: Relevance
“…Subsequent evidence indicated that there is a bone marrow-dependent contribution to eye-associated inflammation (35,36). We confirmed that DBA/2J mice have a point mutation resulting in a premature truncated GPNMB protein (data not shown).…”
Section: The Gpnmb Mutant Mouse Displays Subtle Changes In Myeloid DIsupporting
confidence: 69%
“…Subsequent evidence indicated that there is a bone marrow-dependent contribution to eye-associated inflammation (35,36). We confirmed that DBA/2J mice have a point mutation resulting in a premature truncated GPNMB protein (data not shown).…”
Section: The Gpnmb Mutant Mouse Displays Subtle Changes In Myeloid DIsupporting
confidence: 69%
“…The source of this secreted GDF15 may be the GCL, since GCL was the only cell population in the eye to exhibit increased gene expression after ONC. We also showed increased Gdf15 expression in the retina and increased GDF15 levels in AH of DBA/2J mice, a well-characterized murine chronic glaucoma model (17)(18)(19). Based on these results, we concluded that GDF15 secreted in to the AH by GCL may be a quantifiable measure of glaucomatous neurodegeneration.…”
Section: Discussionmentioning
confidence: 62%
“…The ONC model is an acute axonal injury model, whereas the majority of human glaucoma have chronic features. Although DBA/2J mouse strain is a model of chronic glaucoma, it is considered as pigmentary glaucoma model, in which DCs are known to phagocytose pigment granules in the AS of DBA/2J mice (19). Thus, when we analyze the AH of DBA/2J mice, we have to consider confounding features, including the effect of phagocytic DCs in the AS and inflammation in this model of glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The DBA/2J lacks a fully functional anterior chamber-associated immune deviation, possibly explaining the greater injury response. 11 The immune response in the DBA/2J may be similar to an open-globe trauma without the additional complication of bacterial pathogens since the eye was intact.…”
Section: Introductionmentioning
confidence: 99%